Secular Trends in Global Tides Derived From Satellite Radar Altimetry. Issue 10 (29th September 2022) - Bij de Vaate, I.; Slobbe, D. C.; Verlaan, M.
Abstract: Previous studies have demonstrated that tides are subject to considerable changes on secular time scales. However, these studies rely on sea level observations from tide gauges that are predominantly located in coastal and shelf regions and therefore, the large‐scale patterns remain uncertain. Now, for the first time, satellite radar altimetry (TOPEX/Poseidon & Jason series) has been used to study worldwide linear trends in tidal harmonic constants of four major tides (M2, S2, O1, and K1 ). This study demonstrates both the potential and challenges of using satellite data for the quantification of such long‐term changes. Two alternative methods were implemented. In the first method, tidal harmonic constants were estimated for consecutive 4‐year periods, from which the linear change was then estimated. In the second method, the estimation of linear trends in the tidal constants of the four tides was integrated in the harmonic analysis. First, both methods were assessed by application to tide gauge data that were sub‐sampled to the sampling scheme of the satellites. Thereafter the methods were applied to the real satellite data. Results show both statistically significant decreases and increases in amplitude up to 1 mm/year and significant phase changes up to ∼0.1 deg/year. The level of agreement between altimeter‐derived trends and estimates from tide gauge data differs per region and per tide. Plain Language Summary: Tidal predictions are valuable for many purposes, ranging from processing satellite data to coastal engineering. Although tidal constants are often perceived to be stationary in time, earlier studies have shown that tides are subject to changes both on seasonal and long‐term time scales. However, these studies mainly concern coastal data and therefore, the processes at open ocean remain unclear. The study behind this paper is the first that uses global satellite data to quantify secular trends in tides, thereby filling in the gaps of earlier work. Results show the changes in tides to be significant, with both decreases and increases in tidal amplitude of the order of several centimeters and phase changes of several degrees over the past decades. Key Points: Satellite altimetry has for the first time been used to assess large scale secular trends in global tides Secular trends in the M2, S2, O1, and K1 tides are observed across the globe, with amplitude changes up to ±1 mm/year Global altimetry‐derived trends have magnitudes and spatial variability comparable to estimates at tide gauges